Design of novel Penta core PCF SPR RI sensor based on fusion of IMD and EMD techniques for analysis of water and transformer oil. (January 2022) - Kumar Shakya, Amit; Singh, Surinder
Highlights: Investigating the combination of Gold with Titanium Nitride for refractive index sensing applications. Combination of internal metal deposition (IMD) and external metal deposition (EMD) techniques to deposit Gold and Titanium Nitride at the inner air holes and on the exterior surface of the PCF. Structural arrangement of the air holes in the PCF structure to develop a novel Penta core which is not reported to date to the best of our knowledge. Development of a novel spectroscopy setup to analyze water sample (RI 1.330) and transformer oil sample (RI 1.340) to justify the need for a PCF SPR RI sensor. Abstract: This work presents a "refractive index" sensor based on "photonic crystal fiber" and "surface plasmon resonance" phenomenon. A combination of Gold ( Au ) with Titanium Nitride ( TiN ) is used as a metallic layer in the presented sensor design. Water and transformer oil having R I 1.330 and R I 1.340 are analyzed through a developed spectroscopy setup which lays the condition for the RI sensor designing. A new relationship between transmission (%), absorbance ( AU ), and refractive index ( RI ) is developed and presented in this article. The sensor analysis is performed using the "finite element method" and "perfectly matched layer" conditions. The proposed sensor has obtained a "wavelength sensitivity ( W S ) " of 10000 n m / R I U and 11000 n m / R I U correspondings to TM mode and TE mode, respectively. A high "amplitude sensitivity ( A S ) " of 11280 RIU - 1 and 7550 RIU - 1 is obtained for TM mode and TE mode, respectively. The "sensor resolution ( S R ) " of 1.00 × 10 - 5 R I U and 9.09 × 10 - 6 R I U are reported for TM mode and TE mode, respectively. High linear fitting between resonance wavelength and RI, "full-wave half maximum ( FWHM )" and "figure of merit ( FOM )" are also reported for the proposed sensor. The peak values of the sensing parameters are obtained for R I 1.330 and R I 1.340, corresponding to the TM mode and TE mode, respectively.